Impact of crystallinity towards the performance of semi-polar (11-22) GaN UV photodetector - Supangat, Azzuliani (Tanjung Malim, 2021)
Impact of crystallinity towards the performance of semi-polar (11-22) GaN UV photodetector by Supangat, Azzuliani